Cytotoxic constituents from Boesenbergia pandurata (Roxb.) Schltr - Sukari, Mohd Aspollah; Ching, Amy Yap Li; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Khalid, Kaida (Korean Society of Pharmacognosy, 2007)
Five flavonoid derivatives, pinostrobin (1), pinocembrin (2), alpinetin (3), cardamonin (4) and boesenbergin A (5) were isolated from the rhizomes of Boesenbergia pandurata. All compounds were elucidated based on its spectroscopic data and by the comparison with the previous works. 2D NMR technique was used for the structure elucidation of boesenbergin A to complement the data reported previously. The extracts and pure compounds were screened for cytotoxic activity against HL-60 cancer cell lines (human promyelocytic leukemia). Cytotoxic screening showed most of the extracts and pure compounds isolated from the rhizomes of Boesenbergia pandurata were active against HL-60 cancer cell line. The chloroform extract and boesenbergin A showed the most potent cytotoxic activity.